Magnets-assisted dual-mode triboelectric sensors integrated with an electromagnetic generator for self-sustainable wireless motion monitoring systems. (1st December 2022) - Bhatta, Trilochan; Pradhan, Gagan Bahadur; Shrestha, Kumar; Lee, Sanghyun; Rana, SM Sohel; Sharma, Sudeep; Song, Hyesu; Jeong, Seonghoon; Park, Jae Yeong
Abstract: Self-powered motion sensors are demanded as an energy-efficient technology for future autonomous applications. However, realizing fully self-powered random motion-sensing at a system level is still challenging. Herein, the dual-mode triboelectric nanogenerators (TENGs) are integrated with an electromagnetic generator (EMG) to realize a self-sustained wireless random motion-sensing system. For EMG, a magnetic repulsion mechanism is introduced which equally assists the self-actuation of sliding TENG (S-TENG) and contact separation TENG (CS-TENG) simultaneously. To accomplish self-actuation on CS-TENG, a double-layered flexible thin film of PDMS-FeSiCr/PDMS is used which can simultaneously work as an active TENG layer as well as actuating layer thereby reducing the operational complexity. The motion-sensing resolution and sensitivity of S-TENG are improved by implementing interdigitated electrodes and surface modifications, whereas the self-actuating CS-TENGs offer precise detection of motion directions. The dual-mode TENGs combinedly can measure random motion parameters and motion directions along linear, rotational, and tilting conditions accurately. Moreover, the self-powered motion sensors exhibit excellent acceleration (1.966 V.s 2 /m), frequency (14.099 V/Hz), and tilting angle (0.257 V/degree) sensitivity with greater accuracy. The electricity generated from EMG (peak power: 103.88 mW) is sufficient to operate signal processing and transmission components for self-powered wireless control of the robotic ball balancing platform, showing future possibilities for self-powered autonomous control applications. Graphical Abstract: ga1 Highlights: Magnets-assisted dual mode self-powered TENGs and an EMG for simultaneous energy generation and random motion detection. Double layered ferromagneticfilm as tribonegative as well as self-actuating layer with reduced operational complexity. Excellent frequency, acceleration, and tilting angle sensitivity of the motion sensors along random directions. Energy sufficient for self-sustainable wireless robotic balance control and for future autonomous applications.